The Elementary School Teachers’ Motivational Types and Their Individual Performance Commitment - Gauvin Adlaon; Kautin S Kulano; Erlmarie P Crase; Norquez M Mangindra; Ezra Ivan Rey A Abalos (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This research was conducted to investigate the motivational types of elementary school teachers and their relationship with their individual performance commitment and review scores and their identified demographic profiles. Methodology: Employing a quantitative-correlation research design, a survey was administered to 78 elementary school teachers in Kidapawan City, Philippines. The gathered data underwent rigorous analysis using descriptive and correlational statistics with the Statistical Package for the Social Sciences (SPSS). Main Findings: The results of this study revealed that the respondents exhibited a strong intrinsic motivation, demonstrating unwavering dedication to the teaching profession. Simultaneously, their extrinsic motivations underscored the importance of external incentives and recognition in enhancing their commitment to teaching. This research also showcased the exemplary performance of the respondents in fulfilling their mandated responsibilities, as evident in their IPCR ratings. Further analysis unveiled no significant relationship between the respondents' IPCR scores and their motivational types, whether intrinsic or extrinsic. Novelty/Originality of this study: In general, the outcomes of this research contribute invaluable information for formulating conclusions and practical recommendations. The findings offer insights into the interplay of motivation and performance, which can be applied to enhance teacher support, professional development, and the overall effectiveness of the teaching profession.